Correctional Revitalization: A Systemic Solution for High-Risk Prisoners - Teguh Suroso; Yusuf Saefudin (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
Data from the Directorate General of Corrections on the https://sdppublik.ditjenpas.go.id/ website as of August 2, 2025, recorded that the number of prisoners and detainees in Indonesia reached 281,790. Meanwhile, the total capacity of all correctional institutions (Lapas) in Indonesia can only accommodate 147,530 people. This condition indicates a 90% overcrowding. This overcrowding is a crucial issue because it has the potential to cause disturbances to security and order, such as attempted escapes, controlling drug trafficking from within prisons, the spread of radical ideology, and repeated violations of rules. These behaviors are indicators of an increase in the risk level of prisoners into the high-risk category. The emergence of high-risk prisoners is a serious challenge within the correctional system. In an effort to address this, the Ministry of Law and Human Rights issued Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 35 of 2018 concerning the Revitalization of Correctional Implementation. This policy regulates the development of prisoners based on their risk level. This paper aims to analyze the implementation of the correctional revitalization policy as a systematic solution in handling high-risk prisoners.